Detection and Typing of Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus by Multiplex Real-Time RT-PCR - Wernike, Kerstin; Hoffmann, Bernd; Dauber, Malte; Lange, Elke; Schirrmeier, Horst; Beer, Martin (PLOS ONE, 2012)
Porcine reproductive and respiratory syndrome (PRRS) causes economic losses in the pig industry worldwide, and PRRS viruses (PRRSV) are classified into the two distinct genotypes “North American (NA, type 2)” and “European (EU, type 1)”. In 2006, a highly pathogenic NA strain of PRRSV (HP-PRRSV), characterized by high fever as well as high morbidity and mortality, emerged in swine farms in China. Therefore, a real-time reverse transcription polymerase chain reaction (RT-qPCR) assay specific for HP-PRRSV was developed and combined with type 1- and type 2-specific RT-qPCR systems. Furthermore, an internal control, based on a heterologous RNA, was successfully introduced. This final multiplex PRRSV RT-qPCR, detecting and typing PRRSV, had an analytical sensitivity of less than 200 copies per µl for the type 1-assay and 20 copies per µl for the type 2- and HP assays and a high diagnostic sensitivity. A panel of reference strains and field isolates was reliably detected and samples from an animal trial with a Chinese HP-PRRS strain were used for test validation. The new multiplex PRRSV RT-qPCR system allows for the first time the highly sensitive detection and rapid differentiation of PRRSV of both genotypes as well as the direct detection of HP-PRRSV.